La Narrativisation de la musique - Jean-Jacques Nattiez (Cahiers de Narratologie)
After describing the main features of the literary narrative and demonstrating its analogy with music, the author underlines the necessity not to conider a priori a musical production as a narrative. He analyzes the musical intonation contours as a form of proto-narration which he later explains from the standpoint of Daniel Stern’s developmental psychology. It is then emphasized that music should be considered as a proto-narrative and the authors proposes a criticism of the so-called narratological musicology.